Structural modification from centrosymmetric Rb4Hg2Ge2S8 to noncentrosymmetric (Na3Rb)Hg2Ge2S8: mixed alkali metals strategy for infrared nonlinear optical material design. Issue 9 (5th January 2022) - Tang, Chunlan; Xing, Wenhao; Liang, Fei; Sun, Mengran; Tang, Jian; Lin, Zheshuai; Yao, Jiyong; Chen, Kaixin; Wu, Jieyun; Yin, Wenlong; Kang, Bin
Abstract : A novel noncentrosymmetric chalcogenide (Na3 Rb)Hg2 Ge2 S8 with mixed alkali metals was successfully synthesized and showed a strong second harmonic generation response of 1.4 × AgGaS2 at 2090 nm for infrared nonlinear optics. Abstract : Noncentrosymmetric (NCS) structure is the precondition for second-order nonlinear optical (NLO) materials. In this work, we present a new strategy for constructing NCS structures, whereby mixed alkali metals make a new NCS chalcogenide, (Na3 Rb)Hg2 Ge2 S8, based on the centrosymmetric (CS) Rb4 Hg2 Ge2 S8 . (Na3 Rb)Hg2 Ge2 S8 crystallizes in the polar space group of Pca 21, and adopts a filled cristobalite-type structure with a [HgGeS4 ] 2− ∞ framework formed by the alternating connection of [HgS4 ] and [GeS4 ] tetrahedra via corner-sharing and with the mixed alkali metal cations in the cavities of the framework. Structural analysis and theoretical calculations suggest that the ordered and alternating arrangement of NLO-active chromophores, [HgS4 ] and [GeS4 ] tetrahedra, induced by partial substitution of alkali metals plays an important role in the enhanced second harmonic generation activity. As such, (Na3 Rb)Hg2 Ge2 S8 exhibits strong second harmonic generation response of 1.4 × AgGaS2 at 2090 nm, wide band gap of 2.76 eV and low melting point of 444 °C. Therefore, this strategy of mixed alkali metals may shed light on structural modification from CS to NCS for new NLO materials.